ANALISIS RETURN, ABNORMAL RETURN, AKTIVITAS VOLUME PERDAGANGAN ATAS PENGUMUMAN MERGER DAN AKUISISI (Studi pada Perusahaan yang Listed di BEJ tahun 2000-2002) - SLAMAT HARIJONO ARITONANG; ATIM - DJAZULI; H.M. HARRY - SUSANTO (Wacana Journal of Social and Humanity Studies, 2009)
ABSTRACT   Merger and acquisition events can influence market depend on the existence of the content of informations in the merger and acquisition phenomenon or not. If the merger and acquisition contain informations then market will react and vice versa. Objective of this study is to find out the difference of return, abnormal return, trade volume activity, before, in the moment, after the merger and acquisition announcement. Research sample is determined by the purposive sampling method, and there are 9 companies which announce merger and Acquisition between 2000-2002. Statistical experiment used is T-test experiment (paired two samples for means). The observation was done in 11 day, consist of 5 day before, 1 day in the moment, and 5 day after the merger and acquisition. Results of this research show that there is no significant difference between return in period of the moment, after and before-after merger and acquisition announcement. In the case of abnormal return, there is  no signification difference in the before-at the moment and after period, but before-after periods show the significant difference. The activity of stock’s trade volume suggest no signification difference in the before-at the moment, at the moment - after and before-after periods. Cumulatively, it is concluded that merger and acquisition have no information content,  so that market in general give no reaction, it due to the merger and acquisition announcement can’t give positive signal information   Keywords: Merger , acquisition, return, abnormal return, TVA